Moxibustion for nausea and vomiting in pregnancy - Siti Raihanah; Masrifan Djamil; Sutopo Patria Jati (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Background: Nausea and vomiting are common symptoms that occur for 70-80% of pregnant women. Alternative treatments such as herbal medicine, acupressure and moxibustion have been suggested to control pregnancy-induced nausea-vomiting.Objective: This study is to observe effects of moxibustion at P6 and ST36 point on nausea and vomiting in pregnancy. Methods: This study applied a queasy experimental study by pretest-posttest design on two groups of study. Moxibustion in this study was a heat stimulation technique at P6 and ST36 points for 5 days (7 minutes per day). The P6 point was located on the inner wrist, 2-3 fingers above the wrist between the tendons and the ST36 point was located on 4 fingers below the lower limit of the patella. A random sampling was conducted for 30 pregnant women with gestational age<16 weeks of pregnancy that randomly was divided into 2 groups, or 15 women for each group. Instruments used to measure the nausea and vomiting applied Pregnancy Unique-Quantification of Emesis (PUQE) and B-endorphin.Results: Moxibustion at the P6 point could reduce symptoms of nausea and vomiting (p<0.05). However, Moxibustion at the ST36 point was not effective in reducing symptoms of nausea and vomiting in pregnancy (p>0.05). Conclusion: Moxibustion can more effective at P6 point than at ST36 point in reducing symptoms of nausea and vomiting in pregnancy.